PENGARUH PENGGUNAAN VIDEO ANIMASI INTERAKTIF TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA MATERI NORMA HAK DAN KEWAJIBAN KELAS V DI SD NEGERI 2 BANJARSARI - Baiq Khairun Nisa; Yuniar Lestarini; Rohini; Zalia Muspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Effect of the use of interactive animated videos on student learning interest in Pancasila education, the material on norms, rights, and obligations, Grade V at SDN 2 Banjarsari. The background of this study is based on low student learning interest, as evidenced by a lack of active participation in the learning process and a lack of student interest in Pancasila education material delivered conventionally. The type of research used was an experimental one-shot case study design. The sample was drawn using a saturated sampling technique and there was no control class. The subjects of this study were 20 students. The research instruments used were questionnaires and observations. Based on the data normality test, the population was normally distributed. The results showed that the average interest questionnaire score after the experiment was 46.26. From the results of the calculation of the questionnaire sheet hypothesis test using the One Sample t-test with the help of the SPSS 27.0 application, the calculated t value was obtained at 29.487. If the calculated t is consulted with the t table dk = n-1 = 20 -1 = 19 with a significance level of 5% is 2.093. so it can be concluded from this that the calculated t is greater than the t table (29.487 > 2.093). thus the proposed hypothesis can be accepted, namely "Ho" is rejected and "Ha" is accepted, which means there is an effect of the use of interactive animation videos on increasing student learning interest in learning Pancasila education material on norms, rights and obligations of class V SD Negeri 2 Banjarsari.